2018
DOI: 10.1001/jamacardio.2018.2251
|View full text |Cite
|
Sign up to set email alerts
|

Association of Oral Contraceptives With Drug-Induced QT Interval Prolongation in Healthy Nonmenopausal Women

Abstract: Contraceptive pills are associated with variable drug-induced alterations of ventricular repolarization in healthy nonmenopausal women. Drospirenone, an antiandrogenic pill, was associated with increased sotalol-induced QTc prolongation, although absolute QTc prolongation was modest. This finding was supported by the European pharmacovigilance database, which showed a higher reporting rate of suspected OC-induced ventricular arrhythmias on drospirenone compared with levonorgestrel. More data are required on wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(22 citation statements)
references
References 17 publications
0
21
0
1
Order By: Relevance
“…Fridericia‐corrected QT intervals (QT F ) were found to be significantly shorter in women with congenital adrenal hyperplasia, in which progesterone overexpression occurs, than in healthy female controls . QT F intervals were inversely correlated with serum progesterone concentrations and the ratio of serum progesterone:estradiol concentrations …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Fridericia‐corrected QT intervals (QT F ) were found to be significantly shorter in women with congenital adrenal hyperplasia, in which progesterone overexpression occurs, than in healthy female controls . QT F intervals were inversely correlated with serum progesterone concentrations and the ratio of serum progesterone:estradiol concentrations …”
Section: Discussionmentioning
confidence: 99%
“…In a study of 11 healthy women between the ages of 18 to 32 years, QT intervals were found to be shorter during the luteal phase of the menstrual cycle, when serum progesterone concentrations are highest, compared to those during the follicular phase . Fridericia‐corrected QT intervals (QT F ) were found to be significantly shorter in women with congenital adrenal hyperplasia, in which progesterone overexpression occurs, than in healthy female controls . QT F intervals were inversely correlated with serum progesterone concentrations and the ratio of serum progesterone:estradiol concentrations …”
Section: Discussionmentioning
confidence: 99%
“…In a US retrospective study analyzing 410,782 ECGs from 34,676 women on oral contraceptive pills, QTc was found to be shorter in users of first and second generations than non-users ( p < 0.0001) and longer in users of the fourth generation than non-users ( p < 0.0001) [ 75 ]. In a recent cohort of 498 healthy non-menopausal women, drospirenone was associated with increased sotalol-induced QTc prolongation ( + 6–7 ms) as compared to controls or levonorgestrel [ 16 , 76 ]. Salem et al also confirmed this finding using the European pharmacovigilance database with a disproportionality analysis showing higher reporting rates of suspected diLQTS, ventricular arrhythmias and cardiac arrest for drospirenone vs. levonorgestrel [ 76 ].…”
Section: Exogenous Hormonal Therapy and Its Effect On Qtc Variatiomentioning
confidence: 99%
“…LQTS, BrS and ERS favor different forms of malignant ventricular arrhythmias—for example, TdP for LQTS and ventricular tachycardia for BrS and ERS that may lead to ventricular fibrillation (VF) and, if sustained, SCD [ 3 , 8 , 14 , 15 ]. This sex-specific prevalence of LQTS, BrS and ERS is partly explained by the fact that androgens shorten APD and QT duration, while its deprivation has opposite effects [ 16 , 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…This study is consistent with the clinical QT prolongation by estrogens used for ET. Recently, oral contraceptives were reported to increase the risk of TdP based on the administration of d,l -sotalol to healthy female volunteers [ 16 ]. However, to date, no studies have assessed whether oral contraceptive ingredients affect the hERG channel function.…”
Section: Introductionmentioning
confidence: 99%